Development of bionanocomposite film based on chia seed mucilage incorporated with ZnO nanoparticles and their application for preserving fresh rainbow trout (Oncorhynchus mykiss) fillets - Coban, Ozlem Emir; Jamshidi, Aniseh (Springer, 2024)
In this study, chia seed mucilage was used as the film-forming matrix. The antimicrobial and antioxidant activity of chia seed mucilage films has been attributed to Zn0-NPs. The addition of different concentrations of Zn0-NP (0.25%, 0.5% and 1%) to the chia seed mucilage film matrix significantly affected the mechanical, thermal, antioxidant and antimicrobial properties. It also improved the storage quality of rainbow trout fillets during storage at 4 degrees C for 18 days (p < 0.05). Total mesophilic aerobic bacteria count (TMAB) and thiobarbituric acid (TBA) count of the samples wrapped in chia seed mucilage films containing ZnO-NPs were significantly decreased compared to the control group (p < 0.05). While the shelf life of the samples wrapped with chia seed musilage film (CSM) was 6 days, it was determined as with CSM + 0.25% ZnO-NP CSM + 0.5% ZnO-NP and CSM + 1% ZnO-NP 12, 12 and 15 days, respectively. According to our findings, 1% ZnO-NP added chia seed musilage films can be recommended as a promising new packaging material for fish and fish products industry, especially against oxidative degradation while introducing the product to the market.
Keywords: Active packaging; Chia seed mucilage; Rainbow trout; ZnO nanoparticle